2022
DOI: 10.1364/oe.468458
|View full text |Cite
|
Sign up to set email alerts
|

Study of MXene Ti3C2Tx quantum dot thin film on quartz bulk acoustic wave uncooled infrared sensors

Abstract: The infrared absorption efficiency is essential for an infrared sensor. We propose a quartz bulk acoustic wave (BAW) uncooled infrared sensor coated with MXene quantum dot film. The infrared detection is realized by measuring the resonant frequency of a Y-cut quartz BAW sensitive unit. An infrared sensor is fabricated by MEMS process, then the MXene quantum dot film is coated through the spin coating technology. The mechanism of infrared absorption enhancement is analyzed. Test results show that after coating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…By separating the sensitive and vibrating elements into two parts, signal conversion can be effectively enhanced. In recent years, AlN [100], LiNbO3 [101], metal [99], quartz [102], and SiN [103] have received widespread attention as IR absorption and vibrating elements because of their high IR absorption rates and high sensitivities in terms of the temperature change. In addition to common IR-sensitive materials, Qian et al [104] added a layer of ultrathin graphene on AlN, as shown in figure 7, which not only shows a resonant frequency of 307 MHz and quality factor of 450% of the original but also significantly improves the IR absorption rate based on the subwavelength thickness of the transparent graphene film, increasing it by ten times at 5 µm and possibly a hundred times at 3.4 µm.…”
Section: Resonant Detectormentioning
confidence: 99%
“…By separating the sensitive and vibrating elements into two parts, signal conversion can be effectively enhanced. In recent years, AlN [100], LiNbO3 [101], metal [99], quartz [102], and SiN [103] have received widespread attention as IR absorption and vibrating elements because of their high IR absorption rates and high sensitivities in terms of the temperature change. In addition to common IR-sensitive materials, Qian et al [104] added a layer of ultrathin graphene on AlN, as shown in figure 7, which not only shows a resonant frequency of 307 MHz and quality factor of 450% of the original but also significantly improves the IR absorption rate based on the subwavelength thickness of the transparent graphene film, increasing it by ten times at 5 µm and possibly a hundred times at 3.4 µm.…”
Section: Resonant Detectormentioning
confidence: 99%